The impact of culture on cognitive appraisals: Implications for the development, maintenance, and treatment of posttraumatic stress disorder. (1st July 2018) - Bernardi, Jessica; Engelbrecht, Alberta; Jobson, Laura
Abstract: Objective: Cognitive appraisals have a central role in the development, maintenance, and treatment of posttraumatic stress disorder (PTSD). Accumulating cross‐cultural psychology research has demonstrated that culture affects the way in which an individual cognitively appraises an everyday experience. However, to date, there is little empirical work considering the influence of culture on cognitive appraisals in PTSD and the implications for treatment. The objective of this review article was to consider how culture may impact on the cognitive appraisals central to PTSD. Method: First, we reviewed the role of appraisals in the prominent cognitive models of PTSD. Second, we discussed the cross‐culture psychology literature on the influence of culture on appraisals. Third, we considered the impact of culture on trauma‐related appraisals and associated clinical implications. Finally, we considered implications for the tailoring of clinical treatment for individuals from diverse cultural backgrounds. Results: It was found that culture influences appraisals; a key psychological process highlighted by cognitive models as predictive of PTSD. In particular, cultural differences in self‐understanding influence how individuals appraise experiences in terms of agency, control, mental defeat, and negative independent appraisals of self; appraisals central to PTSD. Conclusions: Empirical work is needed in order to investigate the influence of culture on trauma‐related appraisals in the context of PTSD in order to improve theoretical models and clinical approaches.